Pharmacokinetic interaction of voriconazole and clarithromycin in Pakistani healthy male volunteers: a single dose, randomized, crossover, open-label study - Mushtaq, Mehwish; Fatima, Kshaf; Ahmad, Aneeqa; Mohamed Ibrahim, Osama; Faheem, Muhammad; Shah, Yasar (Frontiers in Pharmacology, 2023)
Background: Voriconazole an antifungal drug, has a potential for drug-drug interactions (DDIs) with administered drugs. Clarithromycin is a Cytochromes P450 CYP (3A4 and 2C19) enzyme inhibitor, and voriconazole is a substrate and inhibitor of these two enzymes. Being a substrate of the same enzyme for metabolism and transport, the chemical nature and pKa of both interacting drugs make these drugs better candidates for potential pharmacokinetic drug-drug interactions (PK-DDIs). This study aimed to evaluate the effect of clarithromycin on the pharmacokinetic profile of voriconazole in healthy volunteers. Methods: A single oral dose, open-label, randomized, crossover study was designed for assessing PK-DDI in healthy volunteers, consisting of 2 weeks washout period. Voriconazole, either alone (2 mg × 200 mg, tablet, P/O) or along with clarithromycin (voriconazole 2 mg × 200 mg, tablet + clarithromycin 500 mg, tablet, P/O), was administered to enrolled volunteers in two sequences. The blood samples (approximately 3 cc) were collected from volunteers for up to 24 h. Plasma concentrations of voriconazole were analyzed by an isocratic, reversed-phase high-performance-liquid chromatography ultraviolet-visible detector (RP HPLC UV-Vis) and a non-compartmental method. Results: In the present study, when voriconazole was administered with clarithromycin versus administered alone, a significant increase in peak plasma concentration (Cmax) of voriconazole by 52% (geometric mean ratio GMR: 1.52; 90% CI 1.04, 1.55; p = 0.000) was observed. Similarly, the area under the curve from time zero to infinity (AUC0-∞) and the area under the concentration-time curve from time zero to time-t (AUC0-t) of voriconazole also significantly increased by 21% (GMR: 1.14; 90% CI 9.09, 10.02; p = 0.013), and 16% (GMR: 1.15; 90% CI 8.08, 10.02; p = 0.007), respectively. In addition, the results also showed a reduction in the apparent volume of distribution (Vd) by 23% (GMR: 0.76; 90% CI 5.00, 6.20; p = 0.051), and apparent clearance (CL) by 13% (GMR: 0.87; 90% CI 41.95, 45.73; p = 0.019) of voriconazole. Conclusion: The alterations in PK parameters of voriconazole after concomitant administration of clarithromycin are of clinical significance. Therefore, adjustments in dosage regimens are warranted. In addition, extreme caution and therapeutic drug monitoring are necessary while co-prescribing both drugs. Clinical Trial Registration:clinicalTrials.gov, Identifier NCT05380245.